Pertangungjawaban Hukum terhadap Pelaku Tindak Pidana Penyalahgunaan Liquefied Petroleum Gas (LPG) Bersubsidi di Indonesia - Shinta Putri Sanjaya; Suwari Akhmaddhian (Savana, 2025)
This study aims to determine how law enforcement is carried out against perpetrators of criminal acts of misuse of Subsidized Liquefied Petroleum Gas (LPG) and how to analyze Court Decision Number 186/Pid.Sus/2024/PN.Cjr Concerning Subsidized Liquefied Petroleum Gas (LPG). The main legal basis governing the management of oil and gas in Indonesia is Law Number 22 of 2001 concerning Oil and Gas. The method used in this study is a normative juridical approach research method, namely reviewing and analyzing the effectiveness of laws and regulations, legal theories and jurisprudence related to the problems discussed. The results of the study indicate that the misuse of subsidized LPG involves criminal sanctions in the form of imprisonment, fines, and revocation of business licenses for corporate actors and has a negative impact on economic stability. The conclusion of this study is that Law Number 22 of 2001 concerning Oil and Gas comprehensively regulates all aspects related to the management of oil and gas. Liquefied Petroleum Gas (LPG) is a vital energy source for Indonesians, particularly for households and small businesses. Legally, misuse of subsidized LPG carries criminal sanctions, including imprisonment, fines, and even revocation of business licenses for corporations, and negatively impacts economic stability. Therefore, firm law enforcement measures and stricter distribution oversight are needed to accurately record subsidy recipients to ensure targeted and effective subsidies, and to consider more efficient direct subsidy mechanisms.